POLITENESS STRATEGIES IN TEACHER-STUDENT INTERACTION IN AN EFL CLASSROOM CONTEXT - Senowarsito Senowarsito (TEFLIN, 2013)
This study explores politeness strategies used by teacher and students in two 90-minute English lessons in a senior high school. The data were video-recorded from two different classroom settings where English is the object and the medium of teaching learning process. The analysis is based on Brown and Levinsonâs politeness strategies. The result shows that teacher and students basically employed positive, negative, and bald on- record strategies. Teacher and studentsâ perception on social distance, the age difference, institutional setting, power, and the limitation of the linguistic ability of the students has contributed to the different choices of polite- ness strategies. The students tend to use some interpersonal function markers. Linguistic expressions that are used in classroom interaction are addressing, encouraging, thanking, apologizing, and leaveâtaking.Â